A mutation in the receptor binding site of GDF5 causes Mohr-Wriedt brachydactyly type A2. Issue 3 (13th July 2005) - Kjaer, K W; Eiberg, H; Hansen, L; van der Hagen, C B; Rosendahl, K; Tommerup, N; Mundlos, S
Abstract : Background: Brachydactyly type A2 (OMIM 112600) is characterised by hypoplasia/aplasia of the second middle phalanx of the index finger and sometimes the little finger. BDA2 was first described by Mohr and Wriedt in a large Danish/Norwegian kindred and mutations in BMPR1B were recently demonstrated in two affected families. Methods: We found and reviewed Mohr and Wriedt's original unpublished annotations, updated the family pedigree, and examined 37 family members clinically, and radiologically by constructing the metacarpo-phalangeal profile (MCPP) pattern in nine affected subjects. Molecular analyses included sequencing of BMPR1B, linkage analysis for STS markers flanking GDF5, sequencing of GDF5, confirmation of the mutation by a restriction enzyme assay, and localisation of the mutation inferred from the very recently reported GDF5 crystal structure, and by superimposing the GDF5 protein sequence onto the crystal structure of BMP2 bound to Bmpr1a. Results: A short middle phalanx of the index finger was found in all affected individuals, but other fingers were occasionally involved. The fourth finger was characteristically spared. This distinguishes Mohr-Wriedt type BDA2 from BDA2 caused by mutations in BMPR1B . An MCPP analysis most efficiently detected mutation carrier status. We identified a missense mutation, c.1322T>C, causing substitution of a leucine with a proline at amino acid residue 441 within the active signalling domain of GDF5. The mutation was predicted to reside in the binding site for BMP type 1 receptors. Conclusion: GDF5 is a novel BDA2 causing gene. It is suggested that impaired activity of BMPR1B is the molecular mechanism responsible for the BDA2 phenotype.